Children's Anxiety Levels Regarding The Impact of Hospitalization At The Army Pematang Siantar Hospital - Norong Perangin-angin; Azis Mangara; Shanty Maria lissanora Fernanda; Riska Wani Eka Putri Perangin-angin; Defri Elias Simatupang (The International Science of Health Journal, 2023)
Hospitalization is a cause of stress for children and their families. However, the level of stressors related to illness and hospitalization differs according to individual children. One child considers it normal while the other child considers it a stressor. The aim of the research is to identify the level of children's anxiety regarding the impact of hospitalization at the Pematang Siantar Army Hospital . The level of children's anxiety is influenced by the seriousness of the child's illness, the presence of invasive actions on the child, hospital environmental factors, and the length of the child's treatment. This research uses a descriptive method. Sample (Hidayat, 2007, p. 32). In this study, there were 30 people who were considered to meet the sample criteria or who were considered representative. The research results showed that the majority of children experienced moderate and severe anxiety, namely 10 people (33.3%) and the minority of children experienced mild anxiety, namely 3 people (10%).